2015
DOI: 10.1002/anie.201502989
|View full text |Cite
|
Sign up to set email alerts
|

A Four‐Component Reaction for the Synthesis of Dioxadiazaborocines

Abstract: A four-component reaction for the synthesis of heterocyclic boronates is reported. Readily available hydrazides, α-hydroxy aldehydes, and two orthogonally reactive boronic acids are combined in a single step to give structurally distinct bicyclic boronates, termed dioxadiazaborocines (DODA borocines). In this remarkable process, one boronic acid reacts as a carbon nucleophile and the other as a boron electrophile to provide enantio- and diastereomerically pure heterocyclic boronates with multiple stereocenters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…It is noteworthy that two boronic acids of similar electronic nature can be used for this four-component transformation, but this requires sequential additions. 128…”
Section: Four-component Petasis Reactionsmentioning
confidence: 99%
“…It is noteworthy that two boronic acids of similar electronic nature can be used for this four-component transformation, but this requires sequential additions. 128…”
Section: Four-component Petasis Reactionsmentioning
confidence: 99%
“…BAs offer attractive opportunities for the discovery of fluorescent supramolecular architectures, since this function may be used to rigidify unreported structures of tridentate π‐conjugated ligands, which can be further tuned, depending on the BA structure. Bearing this in mind, we envisioned that Schiff‐base ligands could be used as a platform to build fluorescent boronates, since the modular structure of these ligands can be specifically engineered to accommodate BAs in form of a conformationally stable π‐conjugated complex (Scheme D) . The result of this design effort is a modular fluorophore platform based on boronic acid salicylidenehydrazone (BASHY) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrazido alcohols S49-4 obtained using this protocol were subjected to a cyclization reaction in relation to the corresponding oxadiazolones and oxazolidinones, that is the target compounds of the work due to their possible antibacterial activity. Later on, the same authors [183] reported a four-component Petasis-type reaction that was used for the synthesis of dioxadiazaborocines.…”
Section: Chemical Transformations Of Indolylboronic Acid Derivativesmentioning
confidence: 99%